KAPASITAS POTENSI PARASITISME Trichogramma sp. (Hymenoptera: Trichogrammatidae) TERHADAP Corcyra sp. - Sumah, Astrid Sri Wahyuni; Kusumadinata, Ali Alamsyah (Jurnal Biosilampari : Jurnal Biologi, 2023)
Parasitism research Trichogramma sp. (Hymenoptera: Trichogrammatidae) has been carried out with the aim of studying the functional response of the parasitoid Trichogramma sp. Functional response is one measure to determine the effectiveness of a predator or parasitoid as an agent in biological control, so that it can express a change in the number of preys attacked by individual predators. Temperature is one of the most important host-parasitoid interactions in functional responses. The method used in the parasitoid parasitism Trichogramma sp. on the host Corcyra sp. using four levels of egg density Corcyra sp. with two different temperature treatments (27OC and room temperature). The results show the functional response model of the parasitoid Trichogramma sp. against its host Corcyra sp. described in the type I model. Parasitization level of Trichogramma sp. showed the same results for both temperature treatments, however, it also shows differences in the speed of predation. It also showed linearity between the parasitoids Trichogramma sp. with the host Corcyra sp. Parasitism rates are still increasing, along with an increase in host density. This research can be a starting point to improve the control of Corcyra sp. using the parasitoid Trichogramma sp. in the field.